2011
DOI: 10.3109/0886022x.2011.552150
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD19+CD5+B Cells and IgA1-positive cells in Tonsillar Tissues of IgA Nephropathy Patients

Abstract: The hallmark of IgA nephropathy (IgAN) is the mesangial deposits of polymeric IgA. However, the source of IgA1 and the mechanism of deposition of IgA1 in the mesangium remain unknown. To better understand its pathogenesis, we investigated the expression of CD19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…CD19+ B cells are believed to be the main sources of IgA production and may contribute to the onset and progression of IgAN 10,11 . In this study, we at first conducted a global RNA sequencing analysis in B cells from patients with IgAN and healthy controls to identify a subset of mRNA transcripts with expression levels correlated with IgAN susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD19+ B cells are believed to be the main sources of IgA production and may contribute to the onset and progression of IgAN 10,11 . In this study, we at first conducted a global RNA sequencing analysis in B cells from patients with IgAN and healthy controls to identify a subset of mRNA transcripts with expression levels correlated with IgAN susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between ST6Gal1 and Gd-IgA1 levels. ST6Gal1 levels showed a significantly positive correlation with Gd-IgA1 levels T score (T0/T1/T2) 21 (42)/24 (48)/5 (10) 23 (46)/22 (44)/5 (10) .92…”
Section: Rst6gal1 Up-regulated C1galt1 Mrna Expression In Pbmcs From ...mentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the reconstitution of IgAN by transfusion of murine spleen cells without CD90+ pan T cells and transfusion of CD19+ cells in SCID mice indicates that the responsible B cells are involved in nephritogenic IgA synthesis in a T-cell-independent manner (181). A Chinese clinical cohort study demonstrated that the levels of tonsillar CD19+CD5+B cells of patients with IgAN were positively associated with the severity of renal histopathology (182). Another study investigated the features of CD19+CD5+ B cells in the circulation, ascites, and biopsy tissues of patients with IgAN.…”
Section: Role Of B Cells In Igan Pathogenesismentioning
confidence: 99%
“…All tonsil stainings were performed on 4-µm paraffin sections as previously described [24]. In brief, immunofluorescence and immunohistochemical stains were performed on formalin-fixed, paraffin-embedded 4-µm sections.…”
Section: Methodsmentioning
confidence: 99%